Low temperature hydrothermal synthesis of calcium phosphate ceramics: effect of excess Ca precursor on phase behavior - Alqap, Asep Sofwan F.; Iis, Sopyan (Council of Scientific and Industrial Research (C S I R), 2009)
Low temperature hydrothermal exchange reaction has been used to synthesize calcium phosphate materials comprising hydroxyapatite and β-tricalcium phosphate using CaO and NH4H2PO4 as calcium and phosphorus precursors respectively. The effect of excess of calcium precursor on phase behaviour of these materials has been investigated by varying CaO content (0, 10 and 20 mole% excess of 0.1 mole CaO) in the suspension. The as-synthesized paste has been dried followed by calcination at 700-1200 ºC. Results show the formation of Ca-deficient apatite at the lower calcination temperature. Excess of CaO shifts the balance to hydroxyapatite formation at the higher calcination temperature such that β-tricalcium phosphate, β-tricalcium phosphate + hydroxyapatite and hydroxyapatite of higher purity are obtained with 0, 10 and 20 mole% excess CaO, respectively.